High performance capacitive deionization using modified ZIF-8-derived, N-doped porous carbon with improved conductivity. Issue 31 (5th June 2018) - Li, Yang; Kim, Jeonghun; Wang, Jie; Liu, Nei-Ling; Bando, Yoshio; Alshehri, Abdulmohsen Ali; Yamauchi, Yusuke; Hou, Chia-Hung; Wu, Kevin C.-W.
Abstract : Zeolitic imidazolate framework (ZIF) composite-derived carbon exhibiting large surface area and high micropore volume is demonstrated to be a promising electrode material for the capacitive deionization (CDI) application. Abstract : Zeolitic imidazolate framework (ZIF) composite-derived carbon exhibiting large surface area and high micropore volume is demonstrated to be a promising electrode material for the capacitive deionization (CDI) application. However, some inherent serious issues ( e.g., low electrical conductivity, narrow pore size, relatively low pore volume, etc .) are still observed for nitrogen-doped porous carbon particles, which restrict their CDI performance. To solve the above-mentioned problems, herein, we prepared gold-nanoparticle-embedded ZIF-8-derived nitrogen-doped carbon calcined at 800 °C (Au@NC800) and PEDOT doped-NC-800 (NC800-PEDOT). The newly generated NC800-PEDOT and Au@NC800 electrodes exhibited notably increased conductivity, and they also achieved high electrosorption capacities of 16.18 mg g −1 and 14.31 mg g −1, respectively, which were much higher than that of NC800 (8.36 mg g −1 ). Au@NC800 and NC800-PEDOT can be promisingly applicable as highly efficient CDI electrode materials.